Escala de independencia espacial de la mesofauna edáfica en un transecto bosque-pastizal del Jardín Botánico Francisco Javier Clavijero - Rueda, Diana Marcela; Negrete Yankelevich, Simoneta; Fragoso González, Carlos (Instituto de Ecología, A.C., 2011)
In order to evaluate the scale of spatial patterns in edaphic mesofauna in a pasture-forest gradient, a collection of soil samples was obtained from a transect, followed by faunal extraction, counting and sorting. Only Sternorrhyncha (except Coccidae) and Coccidae geostatistical analysis showed spatial dependence within the scale 25-500 cm. Results suggest a revision of the current methods of soilfauna sampling, in which sampling intensity and intervals could be optimized for each taxon.